A novel approach to high-pressure gas releases simulations. (September 2021) - Moscatello, Alberto; Uggenti, Anna Chiara; Gerboni, Raffaella; Carpignano, Andrea
Abstract: Risk-relevant plants like Oil & Gas (O&G) or nuclear ones are subjected to strict safety regulations. Risk Assessment is mandatory for these plants, and the damage quantification is a crucial step which has to be carefully addressed. Nowadays the state of practice for consequences estimation entails the use of semi-empirical methods which permit a fast evaluation of the large number of accidental scenarios needed for a Quantitative Risk Assessment (QRA). However, in case of large and congested industrial environments like offshore platforms or equipment inside nuclear primary containment buildings, the aforementioned methods usually lead to an overestimation of the damage areas, for example because they neglect the space congestion which highly affects the accident evolution. A more accurate analysis can be performed using the Computational Fluid Dynamics (CFD), nonetheless its high computational cost represents an important drawback. In this work a CFD approach, called Source Box Accident Model (SBAM), is presented. It models high-pressure gas releases (>10 bar) in congested environments guaranteeing a good computational cost-accuracy compromise. The aim of SBAM is to permit a fast consequences estimation (evaluation of flammable/toxic areas, etc.) via CFD, in order to have a simulations time compatible with the plants design schedule. The long-term objective is to integrate the CFD contribution in a safety driven design process. SBAM is based on the splitting of the multi-physics and multiscale phenomena characterizing the accident: the initial supersonic compressible release and the successive low speed dispersion. The first one is simulated in a small domain called Source Box (SB) and the second one in the case study domain. The two simulations are coupled in a suitable way, through proper parameters which are extensively discussed. This work presents a detailed description of SBAM and two different analyses: a sensitivity study on the coupling parameters and a numerical benchmark which uses a standard CFD simulation as reference. The sensitivity analysis shows that the coupling is a crucial step of the method and the coupling parameters must be treated in the most accurate way. The numerical benchmark shows that SBAM is not introducing significant errors with respect to a standard CFD simulation and, in addition, permits a relevant simplification in the simulation setup and computational cost reduction. Highlights: A novel CFD approach is proposed for accident consequences estimation. The approach is suitable for congested environments (e.g. O&G offshore platforms). The novel approach models accidental high-pressure gas releases via CFD. It allows obtaining accurate and fast results, useful in the plant design phase.